Seamless engineering of location-aware services - Rossi, Gustavo Héctor (2005)
In this paper we present a novel approach to design and implement applications that provide location-aware services. We show how a clear separation of design concerns (e.g. applicative, context-specific, etc) helps to improve modularity. We stress that by using dependency mechanism among outstanding components we can get rid of explicit rule-based approach thus simplifying evolution and maintenance.We first discuss some related work in this field. Next, we introduce a simple exemplary scenario and present the big picture of our architectural approach. Then we detail the process of service definition and activation. A discussion on communication and composition mechanisms is next presented and we end presenting some concluding remarks and further work.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
International Workshop on Context-Aware Mobile Systems, Lecture Notes in Computer Science, October 2005.
Keywords: SERVICIOS BASADOS EN LOCALIZACIÓN; APLICACIONES SENSIBLES AL CONTEXTO; ARQUITECTURAS DE DOMINIO ESPECÍFICO; INGENIERÍA HUMANA